ما مدى إمكانية الاستفادة من الضريبة على التجارة الالكترونية (دراسة ميدانية على مصلحة الضرائب الليبية) (Comprehensive Journal of Science, 2025)
This study aimed to assess the feasibility of applying a tax on e-commerce transactions at the Libyan Tax Authority in the city of Zawiya, and to identify the main factors and obstacles affecting this application. The study adopted a descriptive-analytical approach, with data collection conducted through a questionnaire distributed to a purposive sample of tax authority employees (the sample size was 35 individuals). To analyze the data and test the hypotheses, the one-sample T-test and one-way ANOVA test were used. The results indicated the overall feasibility of benefiting from this tax, with high awareness and understanding among employees of its importance. Conversely, the study showed that the greatest challenge does not lie in awareness but in the lack of internal operational readiness; the null hypothesis related to the availability of resources was accepted, and the results revealed that a severe shortage of training courses is the main source of the problem. The results also confirmed the presence of statistically significant obstacles, most notably the need to amend existing tax laws and regulations. Furthermore, the ANOVA results showed complete homogeneity in employees' opinions regarding the three axes, with no statistically significant differences attributed to demographic variables (qualification, specialization, experience, job). Based on the results, the study recommends issuing the necessary legislative amendments to adapt tax laws to the nature of e-commerce, and simultaneously, implementing an intensive and mandatory training plan to enhance human capacity in the field of digital auditing and collection.
Keywords: E-commerce tax, Libyan Tax Authority, tax awareness, resources, obstacles, digital transformation.